Interlinking humanitarian aid, development cooperation and peacebuilding in displacement contexts: The added value of the HDP nexus' peace component - Nadine Biehler; Barbara Kobler; Amrei Meier (Stiftung Wissenschaft und Politik (SWP), 2023)
Record numbers of violent conflicts are causing growing needs for humanitarian aid, especially in situations of forced displacement. Given the scarcity of resources, many actors seek to provide more effective, efficient and needs-based support. That is also the objective of the humanitarian, development and peace nexus (HDP nexus). The main added value of the HDP nexus in situations of forced displacement lies in its comprehensive perspective on peace, which extends beyond social cohesion and creates space for political solutions and conflict transformation. The latter is a precondition for durable solutions for forcibly displaced people. The German government can actively support this by disseminating and deepening nexus expertise and improving accountability to affected populations.
Keywords: 320; humanitarian aid; development cooperation; peacebuilding; humanitarian; development and peace nexus (HDP nexus); forced displacement; Regional Refugee and Resilience Plan (3RP)